2019
DOI: 10.1002/mrd.23118
|View full text |Cite
|
Sign up to set email alerts
|

Changes in DNA methylation and imprinting disorders in E9.5 mouse fetuses and placentas derived from vitrified eight‐cell embryos

Abstract: Vitrification is increasingly used in assisted reproductive technology (ART) laboratories worldwide, and potential vitrification‐induced risks require further exploration. The effect of vitrification on changes in DNA methylation and imprinting disorders was investigated in E9.5 mouse fetuses and placentas. Fetus and placental tissues were collected from the natural mating (nautural conception [NC]) group, in vitro culture (IVC) group and vitrified embryo transfer (VET) group. The fetal crown‐rump length at E9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Selective loss of DNA methylation of imprinted loci was observed in blastocysts subsequent to fertilization of vitrified bovine and mouse oocytes (Chen, Zhang et al, 2016;Cheng et al, 2014), whereas others found no effect on DNA methylation levels at the H19/IGF2 ICR loci at embryonic day 3 in human ICSI blastocysts following vitrification (Derakhshan-Horeh et al, 2016). When vitrification of mouse embryo at E2.5 (8-cell stage) was paired with IVC, transferred embryos revealed increased levels of global DNA methylation in both E9.5 fetus and placenta compared to IVC, but interestingly were similar to naturally mated derived samples (Ma et al, 2019). The long-term effect of vitrification was further observed in the fetus with increased DNA methylation levels at the imprinted KvDMR1 loci and significant gene expression increase of Dnmt1 and Dnmt3b compared to the IVC and natural mating groups.…”
Section: Art Proceduresmentioning
confidence: 88%
“…Selective loss of DNA methylation of imprinted loci was observed in blastocysts subsequent to fertilization of vitrified bovine and mouse oocytes (Chen, Zhang et al, 2016;Cheng et al, 2014), whereas others found no effect on DNA methylation levels at the H19/IGF2 ICR loci at embryonic day 3 in human ICSI blastocysts following vitrification (Derakhshan-Horeh et al, 2016). When vitrification of mouse embryo at E2.5 (8-cell stage) was paired with IVC, transferred embryos revealed increased levels of global DNA methylation in both E9.5 fetus and placenta compared to IVC, but interestingly were similar to naturally mated derived samples (Ma et al, 2019). The long-term effect of vitrification was further observed in the fetus with increased DNA methylation levels at the imprinted KvDMR1 loci and significant gene expression increase of Dnmt1 and Dnmt3b compared to the IVC and natural mating groups.…”
Section: Art Proceduresmentioning
confidence: 88%
“…In addition, In addition, genes related to foetal growth and development, at the genome-wide methylation level and the methylation level of speci c sites, were disordered in the fresh embryo transfer group, and various methylation levels in the freeze-thaw embryo transfer group similar to the natural pregnancy group. Some researchers [17] have provided an explanation for this phenomenon: freeze-thaw embryo transfer cannot reverse the effect of fresh embryo transfer on embryo gene methylation but will cause a new embryo methylation disorder. Hiuraand et al [18] conducted microarray gene chip analysis on human placenta obtained after freeze-thaw embryo transfer (n=64), fresh embryo transfer (n=16), and natural pregnancy (n=28).…”
Section: Discussionmentioning
confidence: 99%
“…ART treatment can interfere with epigenetic changes, particularly DNA methylation [ 146 ], starting from the preimplantation period in humans and animals [ 147 , 148 ], affecting early embryogenesis and offspring health [ 149 , 150 , 151 ]. The procedures implemented during ART treatment, such as ovarian stimulation using hormones, the in vitro maturation of oocytes and preimplantation embryos, and the use of ICSI and embryo cryopreservation, expose the embryo to environmental conditions that differ from those in spontaneous fertilization and embryogenesis, and which may alter the normal epigenetic mechanisms [ 149 , 152 ].…”
Section: Art and Epigenetic Modificationsmentioning
confidence: 99%